PREDICTION OF PLASMA CONCENTRATIONS FROM FIXED-DOSE COMBINATION FORMULATIONS: IBUPROFEN/PARACETAMOL DRUG PRODUCTS - JOSÉ RAÚL MEDINA-LÓPEZ; JUAN CARLOS RUIZ-SEGURA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: To predict the in vivo performance of ibuprofen and paracetamol (suspension and tablets) using dissolution data of mini-vessels, standard-vessels, United States Pharmacopeia (USP) apparatus IV, and a convolution approach. Methods: The reference suspension was tested with mini-vessels (200 mL of dissolution medium), USP standard-vessels (900 mL at 75 rpm), and USP apparatus IV (laminar flow at 16 mL/min). The reference and a generic formulation (tablets) were tested with USP apparatus II and IV. Both drugs were quantified by an ultraviolet derivative method. Dissolution efficiency, mean dissolution time, t50%, and t80%of tablets were calculated and statistically compared (Student’s t-test). Predicted drug plasma concentrations were calculated. Hypothetical Cmax and area under the concentration-time curve from zero to infinity (AUC0-inf) were compared with real pharmacokinetic values through the calculation of prediction error (PE). PE values should not exceed 10%. Results: Suspension released a range of 94.51–101.07% of ibuprofen and 94.96–101.28% of paracetamol at 60 min among different dissolution methods. Similar profiles between reference and generic tablets were found with the USP apparatus IV (f2=75.51 for ibuprofen and 79.07 for paracetamol). Significant differences were found with all dissolution parameters of the standard-vessels (*p<0.05). The PE values for Cmax of ibuprofen and paracetamol were 7.47 and –8.96%, and for AUC0-inf –0.16 and 0.29% from suspension using the mini-vessels and –1.17 and 1.11% for Cmax and –7.91 and –7.14% for AUC0-inf from reference tablets using the USP apparatus IV. Conclusion: Better predictions were found with the mini-vessels method using dissolution data of suspension and the USP apparatus IV using data from tablets.